A Concept Paper on The Relationship Between Financial Attitudes and Financial Behaviour Among University Students - Ab Wahab, Nur Yuhainis; Zamri, Nur Aisyatul Azra; Abu Hassan, Mohamad Hanif; Ahmad Sabri, Nurul Syazwani (International Business Education Journal, 2025)
Financial attitudes are important in influencing the financial behaviour of individuals, especially students, in order to ensure financial well-being. This is because a good financial attitude will reflect a person's personality in managing finances. Meanwhile, it is difficult for a person to have savings and capital to invest if he does not possess good financial management. This is further demonstrated by the increase in bankruptcy cases among the young generation. Withdrawal of old-age savings through the Employees' Provident Fund (EPF) account is also high in percentage, and the youth's retirement savings show that they cannot sustain beyond three months' salary. The cause of bankruptcy among the young generation is due to the attitude towards money. Awareness of the problems and the importance of financial behaviour in life leads to an investigation of the relationship between financial attitudes and financial behaviour. However, this study will focus on undergraduate students as representatives of the younger generation. Therefore, this study focuses on introducing a conceptual framework related to the relationship between financial attitudes and the level of financial behaviour among undergraduate students. In this study, a quantitative approach with a questionnaire design was used. The sample of the study consists of 376 UPSI students who are continuing their studies in the fields of Bachelor's Degree and Bachelor's Degree in Education, who are in semester one to semester eight. In order to obtain the study sample, the researcher used a stratified sampling technique and the selection of respondents was random. To answer each research question, descriptive analysis and inferential analysis were used. The results of this study may contribute to the government, universities, and the Ministry of Higher Education in the form of strategies and programmes, as well as improving the financial behaviour of students.